Characteristics Of Microencapsulation Of Nades (Natural Deep Eutectic Solvent) Extract Of Senduduk Leaves (Melastoma malabathricum L.) - Almasshabihah, Jihan; Ruri Putri , Mariska; M. Henityo Agung , As’adi (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2026)
Melastoma malabathricum L. (senduduk leaf) is a medicinal plant containing flavonoid compounds such as quercetin, which possess significant antioxidant potential. However, these bioactive compounds are relatively unstable under environmental influences. This study aimed to evaluate the physicochemical characteristics and antioxidant activity of microencapsulated M. malabathricum L. extract obtained using a Natural Deep Eutectic Solvent (NaDES) composed of choline chloride and lactic acid. Extraction was performed using the Ultrasound-Assisted Extraction (UAE) method, followed by microencapsulation with a combination of maltodextrin and gum arabic in three different formulations. Antioxidant activity was assessed using the DPPH method to determine IC₅₀ values, while physical characterization included measurements of particle size, polydispersity index (PDI), and zeta potential. The results showed that Formula 3 had the highest antioxidant activity (IC₅₀ = 12.55 ppm), with particle sizes of 39.5 nm and 453 nm, a PDI of 0.892, and a zeta potential of -45.0 mV, indicating good dispersion stability. Microencapsulation of M. malabathricum L. extract with maltodextrin and gum arabic was effective in enhancing physical stability and preserving antioxidant activity